Project Communication from Start to Finish The Dynamics of Organizational Success - Hynes, Geraldine (Business Expert Press, 2019)
Cover -- Contents -- Acknowledgments -- Chapter 1: Introduction to Project Communication -- Chapter 2: Communication Cornerstones -- Chapter 3: Formal Interpersonal Communication -- Chapter 4: Informal Interpersonal Communication -- Chapter 5: Project Success in a Global Context -- Notes -- References -- About the Author -- Index -- Adpage -- Backcover